PENGARUH OPINI AUDITOR BADAN PEMERIKSA KEUANGAN TERHADAP TINGKAT KORUPSI (STUDI PADA KEMENTERIAN/LEMBAGA DI INDONESIA) - Widodo Prasetyo Utomo; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe aim of this research was to examine the influence of the opinion of theSupreme Audit Agency auditors on the level of corruption. The population in thisstudy are all government ministries / institutions in Indonesia for the period 2012-2016. The sampling technique in this study used purposive sampling and obtained9 ministries / institutions of sample which were used as criteria for ministries /institutions which stumbled on corruption cases for at least 3 years during theperiod 2012-2016. The source of this research data comes from the CorruptionEradication Commission, www.kpk.go.id and the Supreme Audit Agency,www.bpk.go.id. The analytical method used in this study is the classicalassumption test, hypothesis testing and simple linear regression.The results show that: (1) Based on simultaneous testing or F test it isknown that auditor opinion variables have a significant positive effect on the levelof corruption. (2) The auditor's opinion variables have 29.5% implications for thelevel of corruption in ministries / institutions in Indonesia and 70.5% is explainedby other variables not included in this research model. (3) partially auditoropinion variables have a significant positive effect on the level of corruption inministries / institutions in Indonesia for the period 2012-2016.Keywords: Auditor Opinion and Corruption